2020
DOI: 10.1021/acs.macromol.0c00889
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Backbone Rigidity on the Thermomechanical Properties of Semiconducting Polymers with Conjugation Break Spacers

Abstract: There remains a lack of fundamental understanding in the role of backbone rigidity on the thermomechanical properties of conjugated polymers. Here, we provide the first holistic approach to understand the fundamental influence of backbone rigidity on an n-type naphthalene diimide-based conjugated polymer, denoted by PNDI-Cx, through insertion of a flexible conjugation break spacer (CBS). CBS lengths are varied from fully conjugated with zero alkyl spacer (PNDI-C0) to a seven-carbon alkyl spacer (PNDI-C7), with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(104 citation statements)
references
References 55 publications
(93 reference statements)
3
97
0
Order By: Relevance
“…BBL chains exhibit large persistence lengths of up to ≈153 nm (limited by the overall chain length), [ 45 ] whereas the persistence length of the NDI‐T2 backbone appears to be limited to ≈26 nm, regardless of the overall chain length. [ 46 ] We suggest that rigid long chains of BBL extend across amorphous regions connecting multiple crystallites. Although dry AFM and TEM images showed no porosity for BBL in the length scales that we could investigate, we postulate that these inter crystallite disordered regions have enough void space to allow electrolyte intercalation, as evidenced by GISAXS.…”
Section: Discussionmentioning
confidence: 99%
“…BBL chains exhibit large persistence lengths of up to ≈153 nm (limited by the overall chain length), [ 45 ] whereas the persistence length of the NDI‐T2 backbone appears to be limited to ≈26 nm, regardless of the overall chain length. [ 46 ] We suggest that rigid long chains of BBL extend across amorphous regions connecting multiple crystallites. Although dry AFM and TEM images showed no porosity for BBL in the length scales that we could investigate, we postulate that these inter crystallite disordered regions have enough void space to allow electrolyte intercalation, as evidenced by GISAXS.…”
Section: Discussionmentioning
confidence: 99%
“…Among the above‐mentioned approaches, achieving suitable microstructure in all‐PSCs plays a vital role in improving device performance. [ 3,6,20–22 ] However, some major problems, related to the blend morphologies of P D s and P A s, namely the bulk heterojunction (BHJ), which is generally formed during P D ‐ P A mixture solution casting, have been identified in all‐PSCs, including large‐scale demixing of P D / P A domains, [ 8,21 ] unoptimized P D / P A ordering, [ 23,24 ] and misaligned molecular orientation at P D ‐ P A interfaces. [ 25,26 ] Thus, reasonable use of different morphology control strategies, such as modification of molecular structures, [ 5,9,21,27 ] selection of solvent and additive, [ 6,20,28 ] thermal annealing, [ 6,22 ] and so on, to modify domain size and phase purity in all‐PSCs is critical.…”
Section: Introductionmentioning
confidence: 99%
“…2a). As previous studies have demonstrated that the T g increases with increasing chain stiffness, 22 this explains how the P(R F Mi-St) can have a T g Fig. 1 (a) Synthesis of R F Mi (3).…”
Section: Resultsmentioning
confidence: 69%